Effectiveness of Alkali and Acid to Produce Collagen from Fish Skin of Striped Catifish - Devi, Hilda Lu’lu’in Nanda Alfira; Suptijah, Pipih; Nurilmala, Mala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Fish skin is one of the alternative sources contained high protein  to isolate collagen. Fish skin generally extracted by the method of acid, alkali and enzymes. The study aim to determine the effectiveness of NaOHand acetic acid on catfish (Pangasius sp.) skin extraction  process.  The concentrations of alkaline pretreatment were 0,05; 0,1; 0,15 and 0,2 M with the soaking time of 2, 4, 6, 8 and 10 h by NaOH replacement in every 2 h. The concentrations of acetic acid for hydrolisis process were 0.05; 0.1; 0.15 and 0.2 M with the soaking time of 1, 2, and 3 h. The experimental design used for pretreatment process is split splot, while for the hydrolysis process is factorial completely randomized design. The results showed that pretreatment with a concentration of 0.05 M NaOH for 4 h has a significant effect for eliminating non-collagen protein (p